Bridging theory and practice: an index approach to cultivating vocational education teachers in China - Hassan, Aminuddin; Burhanuddin, Nur Aimi Nasuha; Wang, Yixuan (Pegem Akademi Yayincilik, 2024)
This paper introduces an innovative index system aimed at improving the cultivation of early-career teachers in China's higher vocational colleges, a critical sector for bridging the gap between education and industry in the face of China's rapidly evolving economy. Recognizing the unique challenges faced by these teachers, including the dual demands of teaching and industry engagement, and the necessity for professional growth within the vocational education system, this study draws inspiration from existing index systems for vocational education institution management. It proposes a structured framework that emphasizes pedagogical skills, industry engagement, professional networking, and a supportive environment for teacher innovation and growth. Through a comprehensive literature review, the paper identifies key challenges and components essential for successful teacher development, integrating theoretical perspectives from adult learning theory, professional development models, sociocultural theory, and the dual system model of vocational education. The proposed index system focuses on pedagogical proficiency, professional development engagement, industry integration, and community and collegial collaboration, offering a strategic implementation plan to enhance teaching quality and align education with industry needs. The paper discusses the anticipated impact on early-career teacher cultivation, broader applications beyond teacher development, and potential challenges and future directions for implementing the system. By fostering a supportive ecosystem for early-career teachers and focusing on their professional growth, this research aims to contribute significantly to the socioeconomic development of China, enhancing the overall quality of vocational education and its alignment with industry requirements.